ANALYSIS OF THE APPLICATION OF FINANCIAL ACCOUNTING STANDARDS OF ENTITIES WITHOUT PUBLIC ACCOUNTABILITY (SAK ETAP) TO THE FINANCIAL STATEMENTS OF PT. PUSPA LESTARI - Anggi haerani (Review of Accounting and Taxation, 2023)
Purpose - The purpose of this study is to examine how the Accounting Standards for Non-Publicly Accountable Entities (SAK ETAP) are applied to PT's financial statements. LESTARI POPULAR Design/methodology/approach - Primary data obtained directly from PT served as the research methodology and data source for the qualitative descriptive method. LESTARI PUSPA. The testing strategy utilized a purposive inspecting technique with the 2018 fiscal report information. The insightful technique utilized was an expressive examination with a subjective methodology. Finding - The study's findings demonstrated that PT. PUSPA LESTARI introduced balancer reports and pay proclamations that are proper for the SAK ETAP. PT did not present the financial statement notes or the capital report. PT's cash flow statement and PUSPA LESTARI Although it has been presented, PUSPA LESTARI does not yet comply with the SAK ETAP. Originality - the Accounting Standards for Non-Publicly Accountable Entities (SAK ETAP) are applied to PT's financial statements